Infrastructure for ore: Benefits and costs of a not-so-original idea - Louis T. Wells (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
Infrastructure-for-resources deals have been widely criticized, based on few data. But host countries can rigorously compare them with alternatives. Better analysis would lead to better decisions and might convince critics that they can be beneficial, for their financial contributions and for ensuring that resource wealth is converted to productive investment. Still, the deals may pose significant risks for investors.
Keywords: 330